Relationships Between Achievement Goal Orientations, Learning Engagement, and Academic Adjustment in Freshmen: Variable-Centered and Person-Centered Approaches - Wang, Haiying; Xu, Mingxue; Xie, Xiaochun; Dong, Yuan; Wang, Weichen (Frontiers in Psychology, 2021)
Academic adjustment is a principal determining factor of undergraduate students’ academic achievement and success. However, studies pay little attention to freshmen’s antecedent variables of academic adjustment. This study aimed to examine the mechanisms underlying the relationship between achievement goal orientations and academic adjustment in freshmen using variable- and person-centered approaches. A sample of 578 freshmen (aged 18.29±1.04years, 58.5% female) completed questionnaires on achievement goal orientations, learning engagement, and academic adjustment. Latent profile analysis of achievement goal orientations revealed four groups: low-motivation (11.1%), approach-oriented (9.5%), average (52.8%), and multiple (26.6%). In the mediating analysis, results of the variable-centered approach showed that learning engagement mediated the effects of the mastery-approach and performance-avoidance goals on academic adjustment. For the person-centered approach, we selected the average type as the reference profile, and the analysis revealed that compared with the reference profile, learning engagement partially mediated the link between the approach-oriented profile and academic adjustment. The current study highlights the important role that achievement goal orientations and learning engagement play in academic adjustment. We discuss the implications and limitations of the findings.